Vanadium-based zircon microwave dielectric ceramic and preparation method thereof

By preparing vanadium-based zircon microwave dielectric ceramics, the problem of large resonance frequency temperature coefficient in high-frequency applications of existing materials is solved, and the thermal stability and low loss of the device are achieved. It is suitable for microwave devices with 5G/6G communication technology. manufacture.

CN119430928AActive Publication Date: 2025-02-14GUILIN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411633763.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing microwave dielectric ceramic materials have a large problem with the resonant frequency temperature coefficient (τf) in high-frequency and large bandwidth applications, resulting in poor stability of the devices under different temperature environments and difficult to meet the needs of 5G/6G communication technology.

Method used

By preparing a vanadium-based zircon microwave dielectric ceramic, its chemical formula is (Bi0.2La0.2Ce0.2Nd0.2Sm0.2)VO4, the dielectric constant range is 16.1~17.3, and the quality factor (Q×f) value is 41,000~ 47500GHz, the resonant frequency temperature coefficient is +10.5ppm/℃~+13.2ppm/℃, and is prepared by wet grinding, pre-sintering and other steps.

Benefits of technology

It realizes a near-zero resonant frequency temperature coefficient, ensures the thermal stability of the device, and has the characteristics of low loss and suitable for mass production, and is suitable for the manufacturing of various microwave devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430928A_ABST
    Figure CN119430928A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to vanadium-based zircon microwave dielectric ceramic and a preparation method thereof.The vanadium-based zircon microwave dielectric ceramic is prepared from, by weight, Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3, the chemical formula of the vanadium-based zircon microwave dielectric ceramic is (Bi < 0.2 > La < 0.2 > Ce < 0.2 > Nd0. 2Sm < 0.2 >) VO4, powder of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 is obtained based on the components of the vanadium-based zircon microwave dielectric ceramic by weight, and original powder is obtained; stirring and mixing the original powder, performing wet grinding treatment and drying treatment to obtain dried powder, and pre-sintering the dried powder in the air atmosphere to obtain pre-sintered powder; a binder is added into the pre-sintered powder for granulation, compression molding is carried out, sintering is carried out in the air atmosphere, the vanadium-based zircon microwave dielectric ceramic is obtained, the vanadium-based zircon microwave dielectric ceramic has the near-zero resonant frequency temperature coefficient, the thermal stability of a device can be guaranteed, and the service life of the device is prolonged. The method is widely used for manufacturing microwave devices such as various dielectric antenna substrates, resonators and filters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a vanadium-based zircon microwave dielectric ceramic and a preparation method thereof. Background Art

[0002] Microwave dielectric ceramics (MWDC) refer to a new type of functional ceramic material used in microwave frequency band circuits (mainly UHF and SHF bands). Microwave dielectric ceramics have good microwave dielectric properties such as low high-frequency dielectric loss, moderate dielectric constant, and adjustable resonant frequency temperature coefficient. They are the basis and key materials for making microwave electronic components such as dielectric substrates, filters, resonators and oscillators. The three main indicators for measuring the performance of microwave dielectric materials are dielectric constant, quality factor and resonant frequency temperature coefficient.

[0003] With the development of 5G / 6G communication technology, high frequency and large bandwidth characteristics require more dense macro and micro base stations to ensure full signal coverage, which is bound to bring huge market demand for microwave dielectric ceramic materials and components (dielectric antennas, dielectric filters and substrates), and therefore puts forward higher requirements for the selection of microwave dielectric ceramic materials. In order to make the device have a wider frequency selectivity, high signal transmission speed and good stability, high quality factor (Q×f), near-zero resonant frequency temperature coefficient (τ f ) and has a low dielectric constant (ε r <20) microwave dielectric ceramic materials. However, most of the single-phase low dielectric (ε r <20) Ceramics usually exhibit a large negative τ f Value (-20~-80ppm / ℃), such as the ε of cubic spinel structure (Zn / Mg)Al2O4 ceramics r Between 8.5 and 9.0, the Q×f value is as high as 56000 to 100000 GHz, but τ f The value is between -70 and -80ppm / ℃, with low dielectric constant ε r (10~13.5) wolframite structure (Mg / Zn) WO4 ceramics have high Q×f value (62800GHz) and large negative τ f Value (-30~-64ppm / ℃), larger negative τ f The value is not conducive to ensuring the working temperature stability of the device, making it difficult to apply it to the production and use of electronic devices.

[0004] Vanadium-based zircon type (chemical formula AVO4) microwave dielectric ceramics have a low ε r and sintering temperature, higher Q×f value (30000~60000GHz) and adjustable τ f The value of this method has attracted much attention from researchers.1-x Ce x )VO4 and (Bi 1-x Ho x )VO4 can be sintered at a lower temperature and have a near-zero τ by ion substitution. f value. In recent years, high entropy alloys have gradually become a solution for designing high-performance materials in the materials industry. The concept of high entropy comes from HEAs proposed in 2004, which is a single-phase solid solution formed by five or more metal elements in an equimolar ratio. High entropy, lattice distortion, hysteresis diffusion and cocktail effect are introduced to enhance its performance. Therefore, in recent years, a large number of researchers have carried out research on high entropy ceramics, high entropy glasses, and high entropy polymers. It is reported that the solid solution formed by the high entropy effect may obtain performance far higher than that of the original material, so it can be used to develop microwave dielectric ceramic materials with excellent microwave dielectric properties.

[0005] In summary, exploring and developing single-phase low-dielectric microwave dielectric ceramics with near-zero resonant frequency temperature coefficient and low loss to obtain microwave dielectric ceramic materials that can meet diverse practical applications has become a key research direction in this field. Summary of the invention

[0006] The purpose of the present invention is to provide a vanadium-based zircon microwave dielectric ceramic and a preparation method thereof, aiming to develop a single-phase low-dielectric microwave dielectric ceramic with a near-zero resonant frequency temperature coefficient and low loss.

[0007] To achieve the above-mentioned object, in the first aspect, the present invention provides a vanadium-based zircon microwave dielectric ceramic, wherein the composition of the vanadium-based zircon microwave dielectric ceramic comprises Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3, and the chemical formula is: (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4.

[0008] The dielectric constant of the vanadium-based zircon microwave dielectric ceramic is in the range of 16.1 to 17.3, the quality factor is in the range of 41000 to 47500 GHz, and the resonant frequency temperature coefficient is +10.5 ppm / °C to +13.2 ppm / °C.

[0009] In a second aspect, the present invention further provides a method for preparing a vanadium-based zircon microwave dielectric ceramic, which is used to prepare the vanadium-based zircon microwave dielectric ceramic as described in the first aspect above, and is characterized in that it comprises the following steps:

[0010] Based on the composition of vanadium-based zircon microwave dielectric ceramics, powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 are obtained by weighing and mixing to obtain original powder;

[0011] The raw powders are stirred and mixed, and wet-milled and dried in sequence to obtain dried powders, which are pre-sintered in an atmosphere at 800° C. for 4 to 8 hours to obtain pre-sintered powders;

[0012] A binder is added to the pre-sintered powder to form granules, and the granules are pressed into shape. Finally, the granules are sintered in an atmosphere at 850-920° C. for 4-8 hours to obtain vanadium-based zircon microwave dielectric ceramics.

[0013] Wherein, the molar ratio of the Bi2O3, the La2O3, the CeO2, the Nd2O3 and the Sm2O3 is 1:1:1:1:1, the wet grinding treatment time is 6 to 12 hours, and the ball milling medium is anhydrous ethanol.

[0014] Wherein, the binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the added mass of the binder accounts for 3% of the total mass of the original powder.

[0015] The invention discloses a vanadium-based zircon microwave dielectric ceramic and a preparation method thereof. The raw powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 are weighed and wet-grinded according to a proportion, dried and pre-sintered to obtain a pre-sintered powder, and then a binder is added and granulated. After compression molding, the pre-sintered powder is sintered to obtain a vanadium-based zircon microwave dielectric ceramic material having a near-zero positive resonant frequency temperature coefficient. The vanadium-based zircon microwave dielectric ceramic material has a resonant frequency temperature coefficient (τ f ) is close to zero (+10.5~+13.2ppm / ℃), with good temperature stability; its dielectric constant (ε r ) reaches 16.1~17.3, and the quality factor (Q×f) value is between 41000~47500GHz. The preparation method obtains a single-phase, pure-phase (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4 microwave dielectric ceramic material has a near-zero resonant frequency temperature coefficient without the need to add modified materials, which can ensure the thermal stability of the device and can be widely used in the manufacture of various microwave devices such as dielectric antenna substrates, resonators and filters. At the same time, microwave dielectric ceramics are not easy to deliquesce, have a stable crystal structure, and are suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a schematic flow chart of the steps of a method for preparing a vanadium-based zircon microwave dielectric ceramic material having a near-zero positive resonant frequency temperature coefficient prepared in Examples 1-4 of the present invention.

[0018] Figure 2 A vanadium-based zircon microwave dielectric ceramic (Bi) having a near-zero positive resonant frequency temperature coefficient prepared in Example 3 of the present invention 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )X-ray diffraction (XRD) spectrum of VO4.

[0019] Figure 3 A vanadium-based zircon microwave dielectric ceramic (Bi) having a near-zero positive resonant frequency temperature coefficient prepared in Example 3 of the present invention 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )Scanning electron microscope (SEM) surface morphology of VO4.

[0020] Figure 4 The present invention provides a flow chart of a method for preparing vanadium-based zircon microwave dielectric ceramics. DETAILED DESCRIPTION

[0021] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0022] In a first aspect, the present invention provides a vanadium-based zircon microwave dielectric ceramic, wherein the composition of the vanadium-based zircon microwave dielectric ceramic includes Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3, and the chemical formula is: (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4.

[0023] In the embodiment of the present invention, the dielectric constant of the vanadium-based zircon microwave dielectric ceramic is in the range of 16.1 to 17.3, the quality factor is in the range of 41000 to 47500 GHz, the resonant frequency temperature coefficient is +10.5 ppm / °C to +13.2 ppm / °C, and the pure phase (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4 microwave dielectric ceramic material has a near-zero resonant frequency temperature coefficient without the need to add modified materials, which can ensure the thermal stability of the device and can be widely used in the manufacture of various microwave devices such as dielectric antenna substrates, resonators and filters. At the same time, microwave dielectric ceramics are not easy to deliquesce, have a stable crystal structure, and are suitable for mass production.

[0024] See also Figure 1-Figure 4 In a second aspect, the present invention further provides a method for preparing a vanadium-based zircon microwave dielectric ceramic, which is used to prepare the vanadium-based zircon microwave dielectric ceramic as described in the first aspect, and is characterized in that it comprises the following steps:

[0025] S1. Weigh and prepare the ingredients based on the composition of vanadium-based zircon microwave dielectric ceramics to obtain powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 to obtain original powder;

[0026] In an embodiment of the present invention, the molar ratio of the Bi2O3, the La2O3, the CeO2, the Nd2O3 and the Sm2O3 is 1:1:1:1:1.

[0027] S2: stirring and mixing the raw powder, and sequentially performing wet grinding and drying to obtain dried powder, and pre-calcining the dried powder in an atmosphere of 800° C. for 4 to 8 hours to obtain pre-sintered powder;

[0028] In the embodiment of the present invention, the wet grinding treatment time is 6 to 12 hours, and the ball grinding medium is anhydrous ethanol.

[0029] S3: adding a binder to the pre-sintered powder to granulate, pressing and molding, and finally sintering in an atmosphere at 850-920° C. for 4-8 hours to obtain vanadium-based zircon microwave dielectric ceramics.

[0030] In the embodiment of the present invention, the binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the added mass of the binder accounts for 3% of the total mass of the original powder.

[0031] In order to better understand the present technical solution, the following embodiments are provided for further explanation:

[0032] Example 1

[0033] A method for preparing a vanadium-based zircon microwave dielectric ceramic material having a near-zero positive resonant frequency temperature coefficient comprises the following steps:

[0034] (1) The original powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 with purity > 99.9% were prepared by 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 ) The composition of VO4 is weighed and mixed, wherein the molar ratio of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 is 1:1:1:1:1;

[0035] (2) the raw materials in step (1) were wet ball-milled for 6 hours using anhydrous ethanol as the ball-milling medium, and then dried and pre-calcined in an atmosphere at 800° C. for 4 hours;

[0036] (3) Adding a binder to the powder obtained in step (2), granulating the powder, pressing the powder into a shape, and finally sintering the powder at 850° C. in an atmosphere for 4 hours; the binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the amount of polyvinyl alcohol added is 3% of the total mass of the powder.

[0037] Example 2

[0038] A method for preparing a vanadium-based zircon microwave dielectric ceramic material having a near-zero positive resonant frequency temperature coefficient comprises the following steps:

[0039] (1) The original powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 with purity > 99.9% were prepared by 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 ) The composition of VO4 is weighed and mixed, wherein the molar ratio of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 is 1:1:1:1:1;

[0040] (2) the raw materials in step (1) were wet ball-milled for 6 hours using anhydrous ethanol as the ball-milling medium, and then dried and pre-calcined in an atmosphere at 800° C. for 4 hours;

[0041] (3) Adding a binder to the powder obtained in step (2), granulating the powder, pressing the powder into a shape, and finally sintering the powder at 870° C. in an atmosphere for 4 hours; the binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the amount of polyvinyl alcohol added is 3% of the total mass of the powder.

[0042] Example 3

[0043] A method for preparing a vanadium-based zircon microwave dielectric ceramic material having a near-zero positive resonant frequency temperature coefficient comprises the following steps:

[0044] (1) The original powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 with purity > 99.9% were prepared by 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 ) The composition of VO4 is weighed and mixed, wherein the molar ratio of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 is 1:1:1:1:1;

[0045] (2) the raw materials in step (1) were wet ball-milled for 6 hours using anhydrous ethanol as the ball-milling medium, and then dried and pre-calcined in an atmosphere at 800° C. for 4 hours;

[0046] (3) Adding a binder to the powder obtained in step (2), granulating the powder, pressing the powder into a shape, and finally sintering the powder at 890° C. in an atmosphere for 4 hours; the binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the amount of polyvinyl alcohol added is 3% of the total mass of the powder.

[0047] Figure 2 Example 3 is a vanadium-based zircon microwave dielectric ceramic (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4 X-ray diffraction (XRD) spectrum. As can be seen from the figure, (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 The physical phase of VO4 microwave dielectric ceramics is pure tetragonal zircon structure, which is consistent with the PDF card PDF#01-072-0859 of NdVO4. No impurity phase is found, and a single phase material can be obtained. This shows that a preparation method of vanadium-based zircon microwave dielectric ceramics with near-zero positive resonant frequency temperature coefficient is feasible and effective, the preparation method is simple, and the production cost is low.

[0048] Figure 3 A vanadium-based zircon microwave dielectric ceramic (Bi) having a near-zero positive resonant frequency temperature coefficient prepared in Example 3 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm0.2 )VO4 SEM scanning electron microscope image. It can be seen from the figure that the prepared ceramic grain size is uniform, the structure is dense and there is no obvious pores and second phase. This shows that a preparation method for vanadium-based zircon microwave dielectric ceramic material with a near-zero positive resonant frequency temperature coefficient is feasible and effective. This preparation method can obtain relatively dense (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4 microwave dielectric ceramic material.

[0049] Example 4

[0050] A method for preparing a vanadium-based zircon microwave dielectric ceramic material having a near-zero positive resonant frequency temperature coefficient comprises the following steps:

[0051] (1) The original powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 with purity > 99.9% were prepared by 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 ) The composition of VO4 is weighed and mixed, wherein the molar ratio of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 is 1:1:1:1:1;

[0052] (2) the raw materials in step (1) were wet ball-milled for 6 hours using anhydrous ethanol as the ball-milling medium, and then dried and pre-calcined in an atmosphere at 800° C. for 4 hours;

[0053] (3) Adding a binder to the powder obtained in step (2), granulating the powder, pressing the powder into a shape, and finally sintering the powder at 920° C. in an atmosphere for 4 hours; the binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the amount of polyvinyl alcohol added is 3% of the total mass of the powder.

[0054] Furthermore, the present invention uses a cylindrical dielectric resonator method to evaluate microwave dielectric properties. Specifically, the Hakki-Coleman method is used to measure the dielectric constant of solid materials, and εr can only be measured at a resonant frequency corresponding to the TE011 mode. In order to avoid the problem of conduction and radiation losses, the Q value of the microwave dielectric ceramic sample can be measured by the resonant cavity method, and the sample is placed in a low-loss spaced cavity. The resonant frequency temperature coefficient (τf) can be used to measure the stability of devices made of materials under different working environments. It represents the "drift" of the resonant frequency as the temperature changes. The relationship between the resonant frequency and temperature is as follows:

[0055]

[0056] Where f0 is the initial resonant frequency, Δf is the change in resonant frequency, and ΔT is the temperature change. The properties of the prepared microwave dielectric ceramics are shown in Table 1:

[0057] Table 1 Microwave dielectric properties of vanadium-based zircon microwave dielectric ceramics prepared in Examples 1 to 4

[0058]

[0059] As can be seen from Table 1, a vanadium-based zircon microwave dielectric ceramic material with a near-zero positive resonant frequency temperature coefficient is prepared, which has a near-zero resonant frequency temperature coefficient τf (+10.5~+13.2ppm / ℃) and excellent temperature stability; its dielectric constant reaches 16.1~17.3, and the quality factor (Q×f) value is between 41000~47500GHz. In addition, the prepared (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4 microwave dielectric ceramics are single-phase, not easy to deliquesce, with stable crystal structure and suitable for mass production. 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4 microwave dielectric ceramic material has a near-zero resonant frequency temperature coefficient without the need to add modified materials, which can ensure the thermal stability of the device and can be widely used in the manufacture of various microwave devices such as dielectric antenna substrates, resonators and filters. Specifically, it can be used to produce microwave components, including but not limited to microwave resonators, filters, oscillators or dielectric antennas.

[0060] The above disclosure is only a preferred embodiment of a vanadium-based zircon microwave dielectric ceramic and a preparation method thereof of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A vanadium-based zircon microwave dielectric ceramic, characterized in that ; The composition of the vanadium-based zircon microwave dielectric ceramic includes Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3, and the chemical formula is: (Bi 0.2 La 0.2 Ce 0.2 Nd 0.2 Sm 0.2 )VO4.

2. The vanadium-based zircon microwave dielectric ceramic according to claim 1, characterized in that ; The vanadium-based zircon microwave dielectric ceramic has a dielectric constant ranging from 16.1 to 17.3, a quality factor ranging from 41000 to 47500 GHz, and a resonant frequency temperature coefficient ranging from +10.5 ppm / °C to +13.2 ppm / °C.

3. A method for preparing a vanadium-based zircon microwave dielectric ceramic, used to prepare the vanadium-based zircon microwave dielectric ceramic according to any one of claims 1 to 2, characterized in that: The following steps are involved: Based on the composition of vanadium-based zircon microwave dielectric ceramics, powders of Bi2O3, La2O3, CeO2, Nd2O3, Sm2O3 and NH4VO3 are obtained by weighing and mixing to obtain original powder; The raw powders are stirred and mixed, and wet-milled and dried in sequence to obtain dried powders, which are pre-sintered in an atmosphere at 800° C. for 4 to 8 hours to obtain pre-sintered powders; A binder is added to the pre-sintered powder to form granules, and the granules are pressed into shape. Finally, the granules are sintered in an atmosphere at 850-920° C. for 4-8 hours to obtain vanadium-based zircon microwave dielectric ceramics.

4. The method for preparing vanadium-based zircon microwave dielectric ceramics according to claim 3, It is characterized by: The molar ratio of the Bi2O3, the La2O3, the CeO2, the Nd2O3 and the Sm2O3 is 1:1:1:1:1, the wet grinding treatment time is 6 to 12 hours, and the ball milling medium is anhydrous ethanol.

5. The method for preparing vanadium-based zircon microwave dielectric ceramics according to claim 3, It is characterized by: The binder is a polyvinyl alcohol solution with a mass concentration of 5%, and the added mass of the binder accounts for 3% of the total mass of the original powder.

Citation Information

Patent Citations

  • Quentabasic zircon type structure high-entropy oxide ceramic and preparation method thereof

    CN115947599A

  • High-entropy perovskite ceramic material, preparation method thereof and capacitor

    CN118084484A

  • Electrically conductive cerium double oxide ceramics and its production method

    JP3113913B1

Cited By

  • Low-temperature rare earth pyrochlore microwave dielectric ceramic material and preparation method thereof

    CN119930287A

  • Multi-ion co-doped BiVO4-based microwave dielectric ceramic and preparation method thereof

    CN120698780A